Cross-listings and corporate cash savings: International evidence - Kusnadi, Yuanto (Journal of Corporate Finance, 2015)
This paper examines foreign firms that are cross-listed on the U.S. stock exchanges and finds that they exhibit higher cash savings sensitivity to stock price than their non-cross-listed counterparts. This finding is robust even after controlling for alternative regression specifications and samples, country-level institutional infrastructures, different listing types, and the endogeneity of the cross-listing decision. Further cross-sectional tests reveal that the increase in cash savings sensitivity to stock price is more pronounced for firms with stock prices that are more informative, which is consistent with the managerial learning hypothesis. The empirical evidence sheds more light on the implication of the cross-listing decision for international firms' corporate cash management policy.